The Immunoregulation of Th17 in Host against Intracellular Bacterial Infection. (19th March 2018) - Li, Yonghong; Wei, Chaojun; Xu, Hui; Jia, Jing; Wei, Zhenhong; Guo, Rui; Jia, Yanjuan; Wu, Yu; Li, Yuanting; Qi, Xiaoming; Li, Zhenhao; Gao, Xiaoling
Abstract : T helper 17 cells (Th17) constitute a distinct subset of helper T cells with a unique transcriptional profile (STAT3, ROR γ, and ROR α ), cytokine production pattern (IL17 family), and requirement of specific cytokines for their differentiation (TGF- β, IL6, IL21, and IL23). Recent studies involving experimental animals and humans have shown that Th17/IL17 plays a crucial role in host defense against a variety of pathogens, including bacteria and viruses. The underlying mechanisms by which Th17 performs include dendritic cell (DC) regulation, neutrophil recruitment, Th1 modulation, and T regulatory cell (Treg) balance. In recent years, researchers have generated an accumulating wealth of evidence on the role of Th17/IL17 in protective immunity to intracellular bacterial pathogens, such as Mycobacterium tuberculosis and Chlamydia trachomatis, which are one of the most important pathogens that inflict significant socioeconomic burden across the globe. In this article, we reviewed the current literature on the functions and mechanisms by which Th17/IL17 responds to intracellular bacterial infections. A better understanding of Th17/IL17 immunity to pathogens would be crucial for developing effective prophylactics and therapeutics.